Population Redistribution in a Continuously Driven Λ-Type Semiconductor Quantum Dot: Roles of Relaxation-Path Asymmetry And Off-Resonant Coupling - Arik Ramadhan; Bintoro Siswo Nugroho; Asifa Asri; Azrul Azwar; Yudha Arman (Department of Physics, Sebelas Maret University, 2026)
Semiconductor quantum dots (SQDs) exhibit optical responses that are strongly influenced by their internal level structure, relaxation pathways, and excitation intensity. This study investigates the time- and intensity-dependent population dynamics of a continuously driven single -type three-level SQD using the density-matrix formalism within the rotating-wave approximation. Dissipative processes are incorporated through Lindblad-type relaxation terms, while the transient and stationary responses are obtained, respectively, by numerical time integration and steady-state solution of the density-matrix equations. Special attention is given to the relaxation channel and the off-resonant transition dipole moment . The results show that primarily controls the transient redistribution route and the timescale required to reach the stationary regime, whereas the early oscillatory behavior remains dominated by the resonantly driven transition. In the steady-state regime, mainly determines how population leaving the upper state is partitioned between the two lower states, while governs how readily the off-resonant branch becomes active as the driving intensity increases. Consequently, the crossover from predominantly resonant two-level-like behavior to genuine three-level population redistribution is controlled by the combined action of relaxation-path asymmetry and off-resonant coupling strength. These findings provide a clearer mechanism-based interpretation of driven population redistribution in effective multilevel SQD systems.